PENERAPAN MODEL MIND MAPPING DALAM PEMBELAJARAN IPAS MATERI “BUDAYA DI KAMPUNG HALAMAN” PADA KELAS 3 SDN SRONDOL KULON 02 SEMARANG - Ersalwa Herviana Putri; Fani Shela Wati; Veryliana Purnamasari; Nara Puspita Dewi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the application of the Mind Mapping model in the learning of Science on the topic of Culture in Hometown for third-grade students of SDN Srondol Kulon 02 Semarang. This study was motivated by the low involvement of students in learning and the difficulty in understanding the relationship between the cultural concepts being studied. The study used a qualitative descriptive method with 28 third-grade students of SDN Srondol Kulon 02 Semarang as research subjects. Data collection techniques were carried out through observation, documentation, student response questionnaires, and collaborative reflection journals. The application of the Mind Mapping model was carried out by involving students in compiling mind maps about culture in the surrounding environment through the use of keywords, colors, and images. The results showed that the application of the Mind Mapping model was able to increase student involvement in all observed indicators. The activeness of asking questions increased from 32.1% to 82.1%, the ability to express opinions increased from 39.3% to 89.3%, and the ability to connect material with everyday experiences increased from 42.9% to 85.7%. The product analysis results showed that 42.9% of students received a very good rating and 39.3% received a good rating in their Mind Mapping preparation. Furthermore, students responded positively to the learning process, finding it more engaging, creative, and easy to understand. Therefore, the Mind Mapping model can be an effective alternative learning method for elementary school science lessons, enhancing student understanding, engagement, creativity, and collaboration.